2015
DOI: 10.1021/acs.inorgchem.5b01574
|View full text |Cite
|
Sign up to set email alerts
|

From WCl6 to WCl2: Properties of Intermediate Fe–W–Cl Phases

Abstract: Phenomenological studies of WCl6 reduction with transition metal powders M = Mn, Fe, and Co have been recently reported. These reactions involve a series of reductive intercalation steps of M atoms into layered tungsten chloride arrangements, followed by exsolution of MCl2. In the series M = Fe, the presence of divalent iron is evidenced for Fe(x)WCl6, FeW2Cl10, Fe2W2Cl10, and (Fe,W)Cl2 by Mössbauer spectroscopy. Magnetic properties are reported. Bonding characteristics between tungsten atoms in edge-sharing [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Recently, it has been shown that the bioctahedral [W 2 Cl 10 ] n – unit can feature various bonding situations by adopting electrons into W–W bonding energy levels. Bonding and antibonding interactions between the three t 2g d‐orbitals in the bioctahedral [W 2 Cl 10 ] n – ion can be represented by a molecular orbital (MO) scheme following the order of σ < π < δ < δ* < π* < σ* levels with increasing energy …”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Recently, it has been shown that the bioctahedral [W 2 Cl 10 ] n – unit can feature various bonding situations by adopting electrons into W–W bonding energy levels. Bonding and antibonding interactions between the three t 2g d‐orbitals in the bioctahedral [W 2 Cl 10 ] n – ion can be represented by a molecular orbital (MO) scheme following the order of σ < π < δ < δ* < π* < σ* levels with increasing energy …”
Section: Resultssupporting
confidence: 60%
“…A study of the electronic situation of the W–W bonding within edge‐sharing bioctahedra was reported for FeW 2 Cl 10 and Fe 2 W 2 Cl 10 . The [W 2 Cl 10 ] unit in FeW 2 Cl 10 is in the oxidation state 2–, while in Fe 2 W 2 Cl 10 the [W 2 Cl 10 ] unit has the oxidation state 4–, as has been confirmed through the presence of Fe 2+ by Mössbauer spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal scanning of chemical reactions can be a powerful method for the discovery of new compounds when compared to the classical explorative synthesis, where a mixture of solids is reacted at an intuitively selected temperature. The potential of the thermal scanning method has been demonstrated by the identification of more than 20 binary W–I compounds, by solid-state metathesis (SSM) reactions and by scanning a series of reduction reactions of WCl 6 to detect numerous compounds, for example, in the Pb–W–Cl, Co–W–Cl, Fe–W–Cl, and Cu–W–Cl systems. SSM reactions have been successfully employed for the development of metal compounds of nitridoborates, cyanurates, and carbodiimides.…”
Section: Introductionmentioning
confidence: 99%
“…The use of transition metal chlorides and bromides , for the synthesis of cluster compounds is quite typical, while iodides are only rarely used. Recent data for tungsten and rhenium iodides have, however, demonstrated a significant difference of the iodides from the corresponding chlorides and bromides in metal cluster synthesis reactions.…”
mentioning
confidence: 99%